S-nitrosylation of cardiac myocyte proteins may underlie sex differences in cardiac disease - Asamudo, Esther U.; Parackal, Raquel E.; Erickson, Jeffrey R.; Bers, Donald M. (Frontiers in Physiology, 2025)
Nitric oxide (NO) plays several critical roles in cardiovascular physiology. This molecule regulates cardiac function by modifying Ca2+-handling proteins through a process known as S-nitrosylation. These targets include L-type Calcium Channels (LTCC), Ryanodine Receptors (RyR2), Protein Kinase G (PKG), Phospholamban (PLB), sarco/endoplasmic reticulum Ca2+-ATPase (SERCA2a) and Ca2+/Calmodulin-dependent protein kinase II (CaMKII). S-nitrosylation is a covalent attachment of an NO moiety to the thiol side chain of a cysteine residue within a protein. This process can modify excitation-contraction coupling in cardiomyocytes and may mediate some forms of cardioprotection. Several studies have shown that S-nitrosylation may also be involved in the progression of cardiovascular diseases. Most importantly, recent studies have focused on the molecular mechanisms underlying cardiovascular diseases (CVD). Emerging evidence suggests that sex-specific differences in cardiac protein S-nitrosylation exist, and may partially explain disparities in cardiovascular health in males and females. Females have been found to have higher cardiac protein S-nitrosylation levels compared to men, and this is attributed to enhanced NO production through estrogen. Emerging data suggests that S-nitrosylation of specific proteins such as CaMKII has a dual role of promoting and preventing arrhythmias, it is not clear whether the cardioprotective effect of S-nitrosylation of specific cardiac proteins is sex-dependent. A deeper understanding of the mechanisms regulating the role of protein S-nitrosylation and the impact of sex differences on S-nitrosylation will open new avenues for therapeutic interventions in cardiac diseases.